Bioelectricity generation in economic crops at aquaponics system using plant microbial fuel cell - Lajis, Ghaibulna Abdol; Jasni, Jasronita; Kamaruddin, Mohd Faizuddin; Mohd Radzi, Mohd Amran; Azis, Norhafiz; Mohtar, Mohd Nazim (IEEE, 2022)
Sustainability has been one of the most important topics discussed lately-part of sustain ability strategies focusing on global warming and food security issues. Alternative energy sources of various kinds have been explored and applied to mitigate the impact of fossil fuels in the last decade. The electricity generation from living plants has evolved as a new alternative renewable energy source known as a plant microbial fuel cell (PMFC). This paper investigated the bioelectricity generation in economic crops at aquaponics systems using PMFC. The result reveals that economic crops could generate bioelectricity using the PMFC. In the experiment, a single-chamber PMFC configuration was conducted on two economic crops, chilli and okra, with graphite felt as an electrode. As a result, chilli generated 19.58 nW while okra generated 17.00 nW, where chilli outperformed the okra in terms of power generation.